2018 ESC Guidelines for the diagnosis and management of syncope - Kenny, Rose (My University, 2018)
Guidelines summarize and evaluate available evidence with the aim of assisting health professionals in selecting the best management strategies for an individual patient with a given condition. Guidelines and their recommendations should facilitate decision making of health professionals in their daily practice. However, the final decisions concerning an individual patient must be made by the responsible health professional(s) in consultation with the patient and caregiver as appropriate.
PUBLISHED
Keywords: Guidelines, health professionals; Guidelines; Syncope; Transient loss of consciousness; Vasovagal syncope; Reflex syncope; Orthostatic hypotension; Cardiac syncope; Cardiac pacing; Implantable cardioverter defibrillator; Syncope unit; Emergency department; Electrophysiological study; Prolonged ECG monitoring; Tilt testing; Carotid sinus massage; Sudden cardiac death; Ageing